Sensing Peroxynitrite in Different Organelles of Murine RAW264.7 Macrophages With Coumarin-Based Fluorescent Probes - Weber, Maria; Yamada, Namiko; Tian, Xue; Bull, Steven D.; Minoshima, Masafumi; Kikuchi, Kazuya; Mackenzie, Amanda B.; James, Tony D. (Frontiers in Chemistry, 2020)
The elucidation of biological processes involving reactive oxygen species (ROS) facilitates a better understanding of the underlying progression of non-communicable diseases. Fluorescent probes are a powerful tool to study various ROS and have the potential to become essential diagnostic tools. We have developed a series of coumarin fluorescent probes for the selective and sensitive detection of peroxynitrite (ONOO-), a key ROS. Coumarin based probes exhibit good photostability, large Stokes shift and high quantum yields. The three ratiometric probes all contain a boronate ester motif for the detection of ONOO- and a distinctive organelle targeting group. The study of ONOO- generation in a particular organelle will allow more precise disease profiling. Hence, targeting groups for the mitochondria, lysosome and endoplasmic reticulum were introduced into a coumarin scaffold. The three ratiometric probes displayed sensitive and selective detection of ONOO- over other ROS species. All three coumarin probes were evaluated in murine RAW264.7 macrophages for detection of basal and stimulated ONOO- formation.